A rapid Flp-In system for expression of secreted H5N1 influenza hemagglutinin vaccine immunogen in mammalian cells. - Hanxin Lu; Surender Khurana; Nitin Verma; Jody Manischewitz; Lisa King; John H Beigel; Hana Golding (PLoS ONE)
Background Continuing transmissions of highly pathogenic H5N1 viruses in poultry and humans underscores the need for a rapid response to potential pandemic in the form of vaccine. Recombinant technologies for production of immunogenic hemagglutinin (HA) could provide an advantage over the traditional inactivated vaccine manufacturing process. Generation of stably transfected mammalian cells secreting properly folded HA proteins is important for scalable controlled manufacturing. Methodology/principal findings We have developed a Flp-In based 293 stable cell lines through targeted site-specific recombination for expression of secreted hemagglutinin (HA) proteins and evaluated their immunogenicity. H5N1 globular domain HA1(1-330) and HA0(1-500) proteins were purified from the supernatants of 293 Flp-In stable cell lines. Both proteins were properly folded as confirmed by binding to H5N1-neutralizing conformation-dependent human monoclonal antibodies. The HA0 (with unmodified cleavage site) was monomeric, while the HA1 contained oligomeric forms. Upon rabbit immunization, both HA proteins elicited neutralizing antibodies against the homologous virus (A/Vietnam/1203/2004, clade 1) as well as cross-neutralizing antibodies against heterologous H5N1 clade 2 strains, including A/Indonesia/5/2005. These results exceeded the human antibody responses against the inactivated sub-virion H5N1 vaccine. Conclusions/significance Our data suggest that the 293 Flp-In system could serve as a platform for rapid expression of HA immunogens in mammalian cells from emerging influenza strains.